AI and Robotics in Elderly Care: Sustainable Solutions for Aging Populations - Thika Marliana; Dilara Sert Kasim; Samsuni Samsuni; Ton Kiat (Yayasan Adra Karima Hubbi, 2025)
The global rise in aging populations poses urgent challenges to healthcare systems, social welfare, and labor sustainability. Traditional caregiving models are increasingly strained by workforce shortages and escalating medical costs. Artificial Intelligence (AI) and robotics have emerged as transformative technologies offering innovative and sustainable approaches to elderly care. This study aims to examine how AI-driven systems and assistive robots enhance healthcare delivery, autonomy, and quality of life among older adults. Using a mixed-method design, the research combines a systematic review of 120 peer-reviewed studies (2012–2024) with case analyses of robotic implementations in Japan, Sweden, and Singapore. Findings reveal that AI-enabled monitoring, predictive diagnostics, and social robots significantly improve health outcomes, emotional well-being, and caregiving efficiency. However, ethical concerns regarding privacy, human empathy, and digital inequality remain critical barriers to widespread adoption. The study concludes that sustainable elderly care requires integrating technological innovation with human-centered design and policy frameworks that ensure inclusivity, accountability, and data ethics.